Clinical presentation and treatment of multifocal epitrichial sweat gland carcinoma in a horse - Dörner, Cristóbal A.; Castellón, Cristóbal H.; Yañez, Diego (Austral Journal of Veterinary Sciences, 2020)
Epitrichial gland carcinoma is a very rare type of skin tumour in horses. This report describes a horse presenting multiple nodules with associated normal, alopecic and ulcerated skin diagnosed via histopathology as epitrichial gland carcinoma. Treatment consisted of combined surgical excision, topical therapy for ulcerated nodules and cryotherapy for non-ulcerated tumours. Six months following therapy, the excised masses had not regrown and only 10 out of 25 small tumours previously treated with cryotherapy were noticeable.